Magnetic properties of vulcanized natural rubber nanocomposites as a function of the concentration, size and shape of the magnetic fillers - Bellucci, Felipe Silva [UNESP] (2016)
Nickel-zinc ferrites as well as their nanocomposites formed by natural rubber are desirable because they take advantage of the thermal, mechanical and magnetic properties of each component. However, to date, the effect of the size, shape and concentration of the magnetic fillers on the magnetic properties of nanocomposite has not been studied in detail. In this report, we are presenting results about the influence of the geometric characteristic of fillers on the magnetic parameters of nanocomposites. Nickel-zinc ferrite nanopowders (NZF) with stoichiometry Ni0.5Zn0.5Fe2O4 were synthesized by a chemical route named the Modified Polyol Method (MPM) and magnetic nanocomposites were prepared with concentrations between 1 and 10 phr of ferrite nanopowders by thermal compression and hot pressing. From TEM images of ferrite nanopowders aggregates and primary particles in the nanometric scale were identified with aspect ratio different from 1 (r = a/b = 0.99, 0.55 and 0.43). From VSM measurements and particle size, the NZF may be classified as a ferrimagnetic material in a paramagnetic state and the saturation magnetization (MS) was equal to 36.4 emu/g. Performing VSM experiments with different degrees between the sample and the magnetic field, differences up to 9% were identified for the MS indicating a dependence of magnetic parameters on the concentration and shape of particles and aggregates. Magnetization versus time assays were carried out via VSM and two distinct relaxation times were achieved and associated with different populations of size and/or shape for the magnetic fillers. These results point to the possibility of modulation of the magnetic properties of vulcanized natural rubber composites by means of a suitable engineering process to control the concentration, size and shape of magnetic nanoparticles and agglomerates.